2018
DOI: 10.1093/pubmed/fdy137
|View full text |Cite
|
Sign up to set email alerts
|

Association between early prenatal exposure to ambient air pollution and birth defects: evidence from newborns in Xi’an, China

Abstract: Chinese women should avoid exposure to high levels of NO2 and PM10 during the first 3 months of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…The daily concentrations of PM 2.5 , PM 10 , SO 2 , CO, NO 2 and O 3 on the dates between last menstrual period and date of delivery were determined based on maternal residential address. Monthly concentrations for the 3 months prior to pregnancy and the first trimester of pregnancy were estimated for each participant [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The daily concentrations of PM 2.5 , PM 10 , SO 2 , CO, NO 2 and O 3 on the dates between last menstrual period and date of delivery were determined based on maternal residential address. Monthly concentrations for the 3 months prior to pregnancy and the first trimester of pregnancy were estimated for each participant [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…[1014] The study in Xi’an, China, used a generalized additive model to investigate the relationship between birth defects and ambient air pollutants, showed nitrogen dioxide (NO 2 ) increased risk of neural tube defects, congenital heart disease, congenital polydactyly, cleft palate, digestive system abnormalities and gastroschisis, and PM 10 was associated with congenital heart disease and cleft lip with or without cleft palate. [10] The hospital-based case-control study in Fuzhou, China, showed some positive associations between maternal exposure to ambient particles with an aerodynamic diameter of 10 mm or less (PM 10 ) during the first 2 months of pregnancy and fetal cardiovascular malformations. [13] The retrospective cohort study in Anqing city, Eastern China, suggested that exposure to ambient sulfur dioxide (SO 2 ) during pregnancy may increase the risk of birth defects.…”
Section: Introductionmentioning
confidence: 99%
“…However, this association was less evident in the rst trimester (OR = 1.01 [95% CI = 0.98-1.03]). 95% CI = 1.019-1.049) and the highest risks were observed in the second month of pregnancy (RR = 1.031, 95% CI = 1.020-1.042) [24]. More positive associations between PM10 exposure and overall CAs have been observed in Korea and Italy, but these associations were not statistically signi cant [25,26].…”
Section: Discussionmentioning
confidence: 94%